The Effect of a Multi-Sensory Learning and Bilateral Transfer-Based Working Method on Rhythm Skills in Violin Education. - Karakaş Gökçe, Beyza; Dündar, Mehlika (Electronic Turkish Studies)
This study investigates the effect of a practice method based on multisensory learning and bilateral transfer, developed by violinist and educator Prof. Daniel Mason, on the development of rhythmic skills in violin education. Rhythm, regarded as one of the fundamental elements of music, was examined through the simultaneous use of auditory, visual, kinesthetic, and tactile modalities. The study aimed to understand how integrating these sensory systems could contribute to rhythmic perception and performance. A total of ten violin students studying at Gazi University were divided into two equal groups: an experimental group (n=5) and a control group (n=5). The experimental group participated in an 8-week training process that incorporated multisensory and bilateral practices, including playing rhythmic exercises on the piano with the right hand, simultaneous solfège singing, and synchronized finger placement of the left hand on the violin fingerboard. In contrast, the control group continued their practice using conventional methods as they deemed appropriate. Both groups underwent rhythm-focused pre-tests and post-tests. The data were analyzed through the rhythm subdimension of the "Intonation Assessment Form." The findings revealed that the experimental group demonstrated a significant improvement in rhythmic accuracy, structural coherence, and tempo adherence, while the control group showed more limited progress. The results indicate that the multisensory and bilateral transferbased method is an effective approach for enhancing rhythmic skills in violin training. This study emphasizes the potential of a holistic educational model, supported by neuroscience, that transcends traditional violin teaching methods and offers innovative strategies for developing fundamental musical competencies such as rhythm.